Role of ICT In Enabling the Teaching-Learning Process for Attaining Learning Outcomes - Hussain, T. Mohammed (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The education system in India is often criticized for its importance on rote learning, instead of critical thinking and problem-solving. Students are often observed spending most of their time memorizing their lessons, without any thoughts placed on practical applications. But, today accessibility of technology-based learning has been radically creating an upsurge in the inculcation of digital methods in traditional educational roles. Digital Technology includes social media, online games and applications, multimedia, productivity applications, cloud computing, interoperable systems and mobile devices. ICT has a positive impact on students‘ performances in schools, showing a rapid increment in scores compared to those without ICT training. The technology and expertise for digitizing in India are the result of a strong talent pool that is digitally proficient and is well equipped with multimedia and animation skills. Teaching is becoming one of the most challenging professions in our society where knowledge is expanding rapidly and modern technologies are demanding teachers to learn how to use these technologies in their teaching. A teacher plays a pivotal role in the process of teaching learning. Hence, knowledge of ICT and skills to use ICT in teaching /learning has gained enormous importance for today‘s teachers. Teachers are expected to know how to successfully integrate ICT into his/her subject areas to make learning more meaningful. This knowledge development during pre-service training has gained mush importance with the notion that exposure to ICT during this time is helpful in increasing student teacher‘s willingness to integrate technology with classroom teaching. While new technologies increase teachers‘ training needs, they also offer part o the solution. Information and Communication Technology (ICT) can provide more flexible and effective ways for professional development for teachers, improve pre-and in-service teacher training, and connect teachers to the global teacher community. This paper analyses and organizes a variety of approaches found in ICT uses in teacher training into a four-cell matrix. Under the changing scenario, it also discusses the responsibilities and initiatives that the teacher educators must take up for the successful integration of ICT in teacher education. It concludes with discussion of key principles for effective ICT development in teacher education